2014
DOI: 10.1080/09540121.2014.947913
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to prevent HIV transmission: Project Protect intervention for recently infected individuals

Abstract: Past research suggests that as many as 50% of onward human immunodeficiency virus (HIV) transmissions occur during acute and recent HIV infection. It is clearly important to develop interventions which focus on this highly infectious stage of HIV infection to prevent further transmission in the risk networks of acutely and recently infected individuals. Project Protect tries to find recently and acutely infected individuals and prevents HIV transmission in their risk networks. Participants are recruited by com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…Project staff educated affected participants and communities about recent/acute HIV infection, and about the importance of avoiding stigma. As discussed in other articles , neither project staff nor participants in our project and a precursor pilot study in Ukraine reported any increases in stigma‐related problems, but participants did report significantly higher levels of experienced social support at follow‐up than at baseline. Participants were provided with standard counselling and were actively linked to care if appropriate.…”
Section: Methodsmentioning
confidence: 58%
“…Project staff educated affected participants and communities about recent/acute HIV infection, and about the importance of avoiding stigma. As discussed in other articles , neither project staff nor participants in our project and a precursor pilot study in Ukraine reported any increases in stigma‐related problems, but participants did report significantly higher levels of experienced social support at follow‐up than at baseline. Participants were provided with standard counselling and were actively linked to care if appropriate.…”
Section: Methodsmentioning
confidence: 58%
“…Thus, a combination of the expansion of existing harm reduction interventions and the development of new approaches to identify and treat recently infected people should be applied to settings with PWID-driven HIV epidemics [32]. Unfortunately, reaching those recently infected is extremely challenging, especially in settings in which preventive responses have been limited due to the sociopolitical context in which the outbreak arises.…”
Section: Discussionmentioning
confidence: 99%
“…On the other two measures, the proportion of recents in the networks and the incidence of recent infection in the networks, the comparison ratios ranged from 1.6 to 4.2 but the confidence intervals overlapped. Nonetheless, the overall pattern of results provides a proof of concept for the underlying hypothesis that the networks of recents will contain more recents than the networks of longer-term HIV-positives2331.…”
Section: Discussionmentioning
confidence: 77%